2020
DOI: 10.1101/2020.02.03.932491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered conformational sampling along an evolutionary trajectory changes the catalytic activity of an enzyme

Abstract: Several enzymes are known to have evolved from non-catalytic proteins such as solutebinding proteins (SBPs). Although attention has been focused on how a binding site can evolve to become catalytic, an equally important question is: how do the structural dynamics of a binding protein change as it becomes an efficient enzyme? Here we performed a variety of experiments, including double electron-electron resonance (DEER), on reconstructed evolutionary intermediates to determine how the conformational sampling of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 80 publications
7
20
0
Order By: Relevance
“…Previous DEER and double quantum coherence (DQC) EPR studies using small nitroxide spin labels have revealed distinct distance populations for apo and holo MBP with similar widths to those we observed here by time-resolved tmFRET (Selmke et al, 2018). Interestingly, previous NMR and DEER experiments have identified sparsely populated structural states of apo MBP with varying degrees of clamshell closure (Tang et al, 2007;Selmke et al, 2018;Kaczmarski et al, 2020). The existence of several conformations of apo MBP in equilibrium is likely responsible for the larger heterogeneity we observed for apo MBP compared to the maltose-bound state.…”
Section: Discussionsupporting
confidence: 84%
“…Previous DEER and double quantum coherence (DQC) EPR studies using small nitroxide spin labels have revealed distinct distance populations for apo and holo MBP with similar widths to those we observed here by time-resolved tmFRET (Selmke et al, 2018). Interestingly, previous NMR and DEER experiments have identified sparsely populated structural states of apo MBP with varying degrees of clamshell closure (Tang et al, 2007;Selmke et al, 2018;Kaczmarski et al, 2020). The existence of several conformations of apo MBP in equilibrium is likely responsible for the larger heterogeneity we observed for apo MBP compared to the maltose-bound state.…”
Section: Discussionsupporting
confidence: 84%
“…In the X-ray crystal structures of a closely related SBP, AncCDT-1, the difference in Cα−Cα distance (at equivalent positions) between the open (PDB5TUJ) and closed (PDB5T0W) crystallographic states is similar (0.8 nm). 43,44 The difference in the radius of gyration (∼1 Å) between the open and closed crystallographic states of AncCDT-1 was also comparable to that observed between the representative open conformation and the closed crystal structure of DalS. T197Y was modeled into the representative open conformation and the closed crystal structure of DalS using FoldX.…”
Section: ■ Resultssupporting
confidence: 52%
“…The large effect of the T197Y mutation on improving the binding affinities to the three ligands, despite being ∼13 Å from the binding site, was unexpected, prompting further analysis of the molecular basis for this effect. There is no apparent structural explanation for 43,44 To simulate the closed to open conformational transition of DalS (PDB4DZ1), MD simulations (100 ns × 10 replicates) (SI Figure S3) were run with the ligand removed, and clustering analysis was performed to obtain a representative open conformation from the largest cluster. The Cα−Cα distance between residues A85 and K153 (either side of the binding site cleft) and the radius of gyration were calculated for all frames of the simulation (Figure 4A).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Such dynamics plays an important role in allowing for enzyme promiscuity, (i.e., the ability of an enzyme to catalyze multiple, chemically distinct reactions, through either substrate, condition or catalytic promiscuity) and protein moonlighting (i.e., the ability of a protein to perform multiple chemically distinct functions). This, in turn, facilitates enzyme evolvability (the ability of enzymes to acquire new functions), because the introduction of mutations along an evolutionary trajectory can shift the ensemble of conformational states available to an enzyme, allowing it to bind new substrates and facilitate new chemistry. This is significant also in artificial enzyme evolution, since, frequently, directed evolution studies identify residues far from the active site that have significant impact on activity and function, likely by changing the conformational ensemble of the enzyme. , In addition, many enzyme scaffolds (in particular, in the case of TIM-barrel fold proteins , ) possess decorating loops that cover the active site, and there is increasing awareness of the role modulating the dynamics of these loops plays in facilitating enzyme evolvability and the emergence of new functions. , However, there is a caveat to this: a highly “floppy” enzyme can, on the one hand, sample multiple conformational states, allowing for new chemistry to evolve. , On the other hand, if there is too much “floppiness” in the system, it becomes very hard to achieve specificity in transition-state binding. Therefore, optimizing conformational dynamics during evolution requires both allowing the system to have enough flexibility to allow for new chemistry, while simultaneously dampening nonproductive dynamics that can impair the catalytic activity of the enzyme. , …”
Section: Introductionmentioning
confidence: 99%